Population and Diversity of Endophytic Bacteria Associated with Medicinal Plant Curcuma zedoaria - TRI RATNA SULISTIYANI; PUSPITA LISDIYANTI; YULIN LESTARI (Indonesian Society for microbiology, 2014)
Traditionally Curcuma zedoaria (white turmeric) known as herbal medicine which possessing many biological activities. Many endophytic bacteria live in association with their host and may play an important biological roles. The main interest of this study was to investigate the endophytic bacterial diversity associated with white turmeric. White turmerics were collected from three locations in Bogor, West Java, Indonesia. The isolation of endophytic bacteria was carried out using 4 kinds media (Nutrient Agar (NA), NA contained white turmeric extract (NAT), Water Yeast Extract Agar (WYEA), WYEA contained white turmeric extract (WYEAT)), and 2 methods of spread plate and plant piece methods. The identification of selected isolates was conducted by molecular analysis based on 16S DNA. The suitable media and method of isolation endophytic bacteria were NA and spread plate method. A total of 207 bacterial colonies were isolated from rhizomes, stems, and leaves and 73 endophytic bacteria were selected based on morphological characteristics. From them, 32% isolates from Bojong Gede, 22% isolates from Cibinong and 46% isolates from Dramaga were obtained. Endophytic bacteria were predominated 38% in the rhizomes, 32% of stems, and 30% of leaves. Based on 16S rDNA sequence analysis, the isolates were belonging to the cluster Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Firmicutes, and Actinobacteria, with twenty three different genera includes Stenothropomonas, Pseudomonas, Enterobacter, Providencia, Klebsiella, Dickeya, Pantoea, Bacillus, Acinetobacter, Citrobacter, Mycobacterium, Cellulomonas, Microbacterium, Methylobacterium, Penylobacterium, Roseomonas, Agrobacterium, Bosea, Xanthobacter, Rhizobium, Burkholderia, Ralstonia, and Alcaligenes. The plant location, age, part of plant, media and method of isolation seem to influence the endophytic bacterial communities.